The Empathetic EFL Classroom: a Path to Creative Thinking - Vargas Barquero, Vivian (2019)
Contributing to a student’s ability to successfully cope with difficulties depends on several factors. The purpose of this study is to examine the connection between creativity and empathy as the main factors to achieve wellness inside the English as a Foreign Language (EFL) classroom. The ability of students to engage in a successful learning process is accomplished by meeting their needs and creating a relaxing, motivating, and friendly environment. In order to analyze the concept of wellness in regards to the way EFL students feel when they are in class, a survey is generated to examine the perceptions and opinions of two groups of university students from different levels: a group of freshmen and a group of students in the third year of the major Bachillerato en Inglés from Universidad Nacional in Costa Rica. By exploring the participants’ attitudes and responses, the encouragement of creativity and empathy is promoted in the classroom. Consequently, students who feel free and get along with both, classmates and professors, assure that self-expression in a comfortable environment creates a wellness practice, and that it brings plenty of positive consequences to their EFL learning process as well as to their own individual lives.